Myopericarditis in a patient with hepatitis C and cryoglobulinemic renal disease - Ali, Mohamoud A. (Clin Case Rep, 2017)
Although cryoglobulinemia is a well‐appreciated complication of hepatitis C (HC), myopericarditis with resulting pericardial effusion is extremely rare, especially in the absence of a liver transplant. In patients with HC, pericardial effusion with impending tamponade can be a florid and potentially life‐threatening manifestation of multiorgan cryoglobulinemic disease.